Reflective Aspect of Perception and Self-Perception of Subjects in Conflict Interaction - Anikina, V.G.; Lagutin, A.V. (Èksperimentalʹnaâ psihologiâ, 2024)
As part of the experimental study, the change in the images of subjects (the image of oneself and the image of another) included in the conflict interaction was assessed; the relationship between the images of communicants and the level of their reflexivity was revealed. A wide range of methods were used in the work: "Diagnosis of the level of development of reflexivity (A.V. Karpov); scaling Petrovsky - Uvarina, "Who am I?" (M. Kuhn, T. McPartland (modified by T.V. Rumyantseva)). The study was conducted on the "Experiment for studying negotiations" setup (idea by V.A. Lefevre, modification by B.I. Khasan). After the experimental interaction, the participants of the study had significant changes in the assessment of personality traits in terms of "Communicative Self" (T= 2.246 at p≤0.025) were revealed. In subjects with a "low" level of reflexivity, a significant correlation was found between self-identification by a set of characteristics related to the "Active Self" and the perception of characteristics the other (opponent) (r = 0.523 at p≤0.05) In subjects with a "high" level of reflexivity, a significant inverse correlation was determined between the self-identification of the subjects according to the characteristics included in the indicator-component "Communicative Self" (r = - 0.668 at p ≤0.05). The data obtained indicate the existence of a connection between the level of formation of reflexivity, the construction of the image of oneself and the opponent in conflict interaction. В рамках экспериментального исследования оценивалось изменение образов субъектов (образ себя и образ другого), включенных в конфликтное взаимодействие; выявлялась связь между образами коммуникантов и уровнем их рефлексивности. В работе использовался широкий спектр методик: «Диагностика уровня развития рефлексивности (А.В. Карпов); шкалирование Петровского-Увариной, «Кто я?» (М. Кун, Т. Макпартленд (модификация Т.В. Румянцевой)). Исследование проведено на установке «Эксперимент для изучения переговоров» (идея В.А. Лефевра, модификация Б.И. Хасана). После экспериментального взаимодействия у участников исследования было выявлено достоверное изменение в оценке качеств личности по показателю «Коммуникативное Я» (Т = 2,246 при p ≤ 0,025). У испытуемых с «низким» уровнем рефлексивности определена достоверная корреляционная связь между самоидентификацией по набору характеристик, относящихся к «Деятельному Я» и восприятием характеристик Другого (оппонента) (r = 0,523 при p ≤ 0,05). У испытуемых с «высоким» уровнем рефлексивности определена значимая обратная корреляционная связь между самоидентификацией испытуемых по характеристикам, входящим в показатель-компонент «Коммуникативное Я» (r = -0,668 при p ≤ 0,05). Полученные данные указывают на наличие связи между уровнем сформированности рефлексивности, построением образа себя и оппонента в конфликтном взаимодействии.